2019
DOI: 10.1111/1755-0998.12981
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation in a long‐lived seabird (Ardenna tenuirostris) using DNA methylation‐based biomarkers

Abstract: Age structure is a fundamental aspect of animal population biology. Age is strongly related to individual physiological condition, reproductive potential and mortality rate. Currently, there are no robust molecular methods for age estimation in birds. Instead, individuals must be ringed as chicks to establish known‐age populations, which is a labour‐intensive and expensive process. The estimation of chronological age using DNA methylation (DNAm) is emerging as a robust approach in mammals including humans, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 79 publications
3
61
0
Order By: Relevance
“…For example, in humans the tick rate is high until adulthood is reached and then it slows down and remains constant (Horvath, ). In short‐tailed shearwaters, a larger variability in DNA methylation was found at younger ages, although the few samples of young birds was a limiting factor for this study (Paoli‐Iseppi et al, ). In the European sea bass, by contrast, we had a large number of juvenile individuals of less than 1.5 years.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in humans the tick rate is high until adulthood is reached and then it slows down and remains constant (Horvath, ). In short‐tailed shearwaters, a larger variability in DNA methylation was found at younger ages, although the few samples of young birds was a limiting factor for this study (Paoli‐Iseppi et al, ). In the European sea bass, by contrast, we had a large number of juvenile individuals of less than 1.5 years.…”
Section: Discussionmentioning
confidence: 97%
“…This modification is found at 60-80% of CpG sites (where a cytosine, C, is next to a guanine, G, in the DNA sequence) across vertebrate genomes (Jones, 2001(Jones, , 2012 both at gene bodies and promoters (Deaton and Bird, 2011), participating in the regulation of gene expression in response to developmental and environmental signals (Eirin-Lopez and Putnam, 2018). Most importantly, it has been shown that the %DNA methylation at specific positions of certain genes correlates linearly with chronological age, making age prediction reliable as demonstrated in the case of mammals including humans (Grönniger et al, 2010;Polanowski et al, 2014), as well as in other vertebrates (Paoli-Iseppi et al, 2019). This property has boosted the development of epigenetic aging tools that are now being successfully used in human forensics (Horvath, 2013;Shabani et al, 2018) as well as in marine organisms (Polanowski et al, 2014;Eirin-Lopez and Putnam, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the second for a wild bird population that suggests methylation varies with age. Humans have an epigenetic clock where methylation increases with age (Horvath 2013), but waterthrush generally displayed decreased methylation with age, similar to that found in a seabird at most age-related restriction sites (De Paoli-Iseppi et al 2018). In addition to methylation varying with pollutant concentrations as previously seen in a wild bird population (Romano et al 2016), our study is the first for a wild bird population to suggest a potential sex-specific epigenetic response to contaminants.…”
Section: Discussionsupporting
confidence: 76%
“…5b) I hypothesized older adults to have fewer methylated restriction sites than younger adults because decreased methylation is correlated with age in birds (De Paoli-Iseppi et al 2019). Similarly, I expected nestlings to be differentially methylated from adults.…”
Section: ) A)mentioning
confidence: 99%